Conductive silver adhesive with high heat resistance and high thermal conductivity and preparation method thereof
By using the composite technology of tetrafunctional epoxy acrylate oligomer and modified silver nanomaterials in conductive silver glue, the problems of insufficient heat resistance and electrical conductivity of conductive silver glue are solved, and the effects of high heat resistance, high heat conductivity and excellent electrical conductivity are achieved.
Patent Information
- Application Number
- CN202411974036.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The existing conductive silver glue has poor heat resistance, poor dispersion of conductive particles in the matrix, resulting in insufficient conductivity and thermal conductivity. High fill volume conductive particles lead to complex process, poor bonding strength and high price.
A tetrafunctional epoxy acrylate oligomer was used as the matrix material, and a maleic anhydride modified imidazole curing agent and a curing accelerator were combined, and a silver nanocomposite particles with core-shell structures of nanosilver particles were coated with polyaniline and modified silver nanowires. High heat resistance and high heat conduction conductive silver glue was prepared by vacuum stirring and vacuum filling technology.
It realizes the high heat resistance of conductive silver glue (more than 180℃), excellent thermal conductivity, improves conductivity and bonding strength, reduces the cost of raw materials, and broadens the scope of use.
Smart Images

Figure BDA0005220031050000021 
Figure BDA0005220031050000071 
Figure FDA0005220031040000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic materials, and in particular relates to a highly heat-resistant and highly thermally conductive conductive silver paste and a preparation method thereof. Background Art
[0002] Conductive adhesive is an adhesive that has certain conductive properties after curing or drying. It usually has a base resin and conductive fillers, i.e. conductive particles, as its main components. The conductive particles are combined together through the bonding effect of the base resin to form a conductive path, thereby achieving conductive connection of the bonded materials.
[0003] In the prior art, common matrix resins generally include polyurethane resin, acrylic resin, chloroacetic resin, epoxy resin, etc. Among them, epoxy resin is widely used due to its excellent adhesion and medium and low temperature curing conditions. However, there are the following problems: First, the heat resistance is poor. The conductive silver paste generally uses epoxy resin as the matrix, and its general heat resistance is 100-150°C, which greatly limits the use temperature and application range of the material and cannot meet the needs of the high-end market; second, the conductive particles are poorly dispersed in the epoxy resin, and the interface contact is insufficient, which affects the construction of the conductive path and its density, so that the conductivity still needs to be further improved; in addition, in order to form enough conductive networks and thermal conductive networks, the existing conductive silver paste based on the silver powder system must increase the mass fraction of the conductive particles in the conductive silver paste, generally using more than 70%, or even up to 90%, in order to meet the conductivity requirements. The conductive silver paste with a high filling amount of conductive particles not only cannot achieve a good thermal conductivity, but also brings the disadvantages of complex mixing process, poor bonding strength and high price.
[0004] In addition, due to the rapid development of miniaturization and micro-miniaturization of electronic components and high density and high integration of printed circuit boards, higher requirements are placed on the comprehensive performance of conductive silver paste; for example, with the development of 5G technology, face recognition, optical communication and image processing, the heat generated by related chips is increasing. The thermal conductivity of traditional silver paste can no longer meet the growing demand for heat dissipation. It is urgent to develop conductive silver paste that not only has excellent electrical conductivity but also excellent thermal conductivity, so as to improve the heat dissipation efficiency and stability of the chip. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a highly heat-resistant and highly thermally conductive conductive silver paste, aiming to solve the technical problems of poor comprehensive performance of traditional conductive silver paste, such as low cost, bonding strength, electrical conductivity, thermal conductivity and stability.
[0006] The invention also provides a method for preparing the highly heat-resistant and highly thermally conductive conductive silver paste.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A highly heat-resistant and highly thermally conductive conductive silver paste comprises the following components in parts by weight: 100 parts of a tetrafunctional epoxy acrylate oligomer, 100-350 parts of conductive particles, 3-8 parts of a sintering aid, 60-80 parts of a curing agent, and 5-15 parts of a curing accelerator, wherein the molecular structure of the tetrafunctional epoxy acrylate oligomer is:
[0009]
[0010] In some specific embodiments, the curing agent is a maleic anhydride modified imidazole curing agent;
[0011] In certain specific embodiments, the conductive particles include a mixture of silver nanocomposite particles and silver nanowires in a mass ratio of 1:(2-5); wherein the particle size of the silver nanocomposite particles is 5-30 nm; and the size of the silver nanowires is 5-10 nm.
[0012] In some specific embodiments, the silver nanocomposite particles are obtained by the following preparation method:
[0013] . Sodium hypophosphite is dissolved in distilled water and dispersed uniformly by ultrasonication, and then a nitric acid solution containing aniline is added to the solution to prepare a reducing solution; silver nitrate is weighed and dissolved in water and added to the nitric acid solution and stirred uniformly to prepare an oxidizing solution, which is then added dropwise to the reducing solution to prepare nanosilver particles, and the reaction is carried out by stirring;
[0014] b. After the reaction in step a is completed, the reaction system is moved to room temperature. After the system temperature stabilizes, an aqueous solution containing nitric acid and ammonium persulfate is added dropwise to the reaction solution to initiate in-situ polymerization of aniline to obtain a polyaniline / silver nanocomposite material, namely, silver nanocomposite particles.
[0015] In some specific embodiments, the silver nanowires are pretreated by the following method: adding octadecyl-polyethylene glycol-thiol to water, stirring and dispersing evenly, soaking the silver nanowires in the aqueous solution of octadecyl-polyethylene glycol-thiol, then heating and drying at 60-80°C, and then soaking in water again, repeating three to five times, and finally heating and drying at 60-80°C to obtain the modified silver nanowires.
[0016] In some specific embodiments, the sintering aid is a silane coupling agent, and the silane coupling agent is one or a mixture of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, and vinyltriethoxysilane.
[0017] In certain specific embodiments, the curing accelerator is at least one of 2,4,6-tris(dimethylaminomethyl)phenol, o-hydroxybenzyldimethylamine, benzyldimethylamine or nonylphenol.
[0018] A method for preparing the aforementioned highly heat-resistant and highly thermally conductive conductive silver paste is characterized by comprising the following steps:
[0019] 1) preparing modified silver nanowires;
[0020] 2) Preparation of polyaniline / silver nanocomposites;
[0021] 3) According to the formula requirements, the modified silver nanowires in step 1) and the polyaniline / silver nanocomposite material prepared in step 2) are mixed uniformly to obtain component A;
[0022] 4) mechanically stirring the tetrafunctional epoxy acrylate oligomer, sintering aid, curing agent and curing agent accelerator at room temperature at a speed of 500-1000 r / min for 10 min to prepare component B;
[0023] 5) First add component B in a planetary vacuum mixer at room temperature, then add component A in 2-5 times, stir for 5-15 minutes after each addition, wherein the rotation speed is 300-800 r / min, the revolution speed is 800-1500 r / min, and the vacuum degassing mode is turned on during stirring to obtain a conductive rubber material;
[0024] 6) The conductive adhesive prepared in step 5) is injected into a syringe through a vacuum filling machine to obtain a product - a highly heat-resistant and highly thermally conductive conductive silver adhesive.
[0025] Compared with the prior art, the present invention has at least the following advantages:
[0026] 1) The conductive silver paste provided by the present invention adopts a tetrafunctional epoxy acrylate oligomer as a matrix material, and is compounded with a maleic anhydride-modified imidazole curing agent and a curing accelerator, so that the prepared conductive silver paste has an excellent curing time, and can be cured at a curing temperature of 130°C. The prepared conductive silver paste system and its heat resistance exceed 180°C and reach 225°C; at the same time, the use of a tetrafunctional epoxy acrylate oligomer also makes the prepared conductive paste have excellent chemical resistance, high glass transition temperature (Tg) and low shrinkage, further improving the reliability of the conductive paste;
[0027] 2) The conductive silver paste provided by the present invention uses polyaniline-coated silver nanoparticles with a core-shell structure, which not only effectively reduces the density of silver nanoparticles and effectively solves the problem of conductive particle sedimentation during mixing, stirring and processing of silver nanoparticles, but also significantly improves the compatibility of silver nanoparticles in the epoxy resin system and greatly improves the uniform dispersibility of silver nanocomposite particles in the epoxy resin system;
[0028] 3) The conductive silver paste provided by the present invention modifies the silver nanowires by octadecyl-polyethylene glycol-thiol, so that the surface of the silver nanowires has hydroxyl and thiol. The silver nanowires containing hydroxyl and thiol react with the active groups in the epoxy resin and the curing agent to form a three-dimensional network structure, which effectively improves the compactness of the silver nanowires in the epoxy resin, and then effectively improves the conductive performance of the silver nanowires in the epoxy resin system. At the same time, the octadecyl group on the surface of the modified silver nanowires effectively improves the compatibility of the silver nanowires with the epoxy resin, so that the silver nanowires are evenly dispersed in the epoxy resin system, and the establishment of the conductive path is further improved.
[0029] 4) The conductive silver paste provided by the present invention adopts tetrafunctional epoxy acrylate oligomer, compounded with polyaniline-coated nano-silver particles of core-shell structure silver nanocomposite particles and modified silver nanowires, wherein multifunctional epoxy resin-tetrafunctional epoxy acrylate oligomer is adopted to improve the compactness of the matrix system; and by adopting the modified silver nanowire, the dispersibility of the silver nanowire in the silver paste system is improved, and the compactness of the conductive silver paste system is further improved, so that the active groups on the surface of the modified silver nanowire react with the active groups in the epoxy resin system to form a three-dimensional network structure, thereby improving the glass transition temperature of the conductive silver paste; and then combined with epoxy The resin system has a core-shell structure of polyaniline-coated nano-silver particles with excellent compatibility, and the silver nanocomposite particles with core-shell structure are filled into the gaps of the silver nanowires, thereby increasing the conductive path or forming more parallel conductive paths in the silver glue, thereby reducing the amount of conductive particles filled, and greatly improving the conductive performance and conductive stability of the conductive silver glue; at the same time, when preparing the conductive silver glue of the same magnitude, the amount of silver powder added can be reduced, so that the price of the conductive silver glue is reduced by 100-300%, effectively reducing the raw material cost of the existing conductive silver glue; and the silver colloid with low silver content can also improve the product stability of the silver glue system, optimize the bonding strength and toughness of the silver glue, and greatly broaden the application range of the silver glue. That is, by using a tetrafunctional epoxy acrylate oligomer, compounding the silver nanocomposite particles with core-shell structure of polyaniline-coated nano-silver particles and the modified silver nanowires, the synergistic effect makes the conductive silver glue system have excellent heat resistance, thermal conductivity, conductivity and bonding properties. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with specific embodiments. The following embodiments are merely illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0031] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0032] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0033] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0034] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.
[0035] In the following embodiments, the molecular structure of the tetrafunctional epoxy acrylate oligomer used is:
[0036] It can be purchased from commercial sources or prepared by a synthetic method in the art.
[0037] The curing agent is a maleic anhydride modified imidazole curing agent, NPA-305 product purchased from Jiadesheng Technology Co., Ltd.;
[0038] Wherein, the silver nanocomposite particles are obtained by the following preparation method:
[0039] a. Dissolve 3g of sodium hypophosphite in 400ml of distilled water and disperse evenly by ultrasonication for 10min, then add 45ml of nitric acid solution (1M / L) containing 4.8g of aniline to the solution to prepare a reducing solution; weigh 1.5g of silver nitrate, dissolve it in 100ml of water, add 10ml of nitric acid solution (1M / L) and stir evenly to prepare an oxidizing solution, and add it dropwise to the reducing solution at a rate of 10 to 15 drops / min to prepare nanosilver particles. Keep stirring during the experiment, and the reaction is carried out in 40℃ water for 90min;
[0040] b. After the reaction in step a is completed, the reaction system is moved to room temperature. After the system temperature stabilizes, 100 ml of an aqueous solution containing 10 ml of nitric acid (1 M / L) and 7.5 g of ammonium persulfate is added dropwise to the reaction solution to initiate in-situ polymerization of aniline for 5 hours to obtain a polyaniline / silver nanocomposite material with a particle size of 5-30 nm, i.e., silver nanocomposite particles.
[0041] The silver nanowires were pretreated by the following method: 20 ml of octadecyl-polyethylene glycol (molecular weight 600)-thiol (purchased from Guangzhou Carbon Water Technology Co., Ltd.) was added to 150 ml of water, stirred and dispersed evenly, the silver nanowires were immersed in 150 ml of octadecyl-polyethylene glycol (molecular weight 600)-thiol aqueous solution for 15 minutes, then heated and dried at 75°C, and then immersed in 150 mL of octadecyl-polyethylene glycol-thiol aqueous solution for 10 minutes, heated and dried at 75°C, and repeated three times. After the last heating and drying at 80°C, the modified silver nanowires were obtained, and the size of the silver nanowires was 5-10 nm.
[0042] The test methods used in the following embodiments include:
[0043] By testing the main properties of each test sample respectively, the heat resistance, electrical conductivity and thermal conductivity of the prepared conductive silver paste can be reflected; the main properties tested in this application include heat resistance, volume resistivity, conductivity coefficient, Tg glass transition temperature, storage stability, etc.
[0044] 1. Glass transition temperature test:
[0045] The glass transition temperature test was performed using an SMN-R fully intelligent reflectivity instrument and differential scanning calorimetry according to the DSC method specified in IPC-TM-6502.4.25.
[0046] 2. Thermal decomposition temperature (Td) test
[0047] The thermal decomposition temperature of the samples was tested using a thermogravimetric analyzer (TGA) according to the method described in IPC-TM-650 2.4.24.
[0048] Example 1
[0049] This embodiment provides a method for preparing a conductive silver paste with high heat resistance and high thermal conductivity, which comprises the following steps:
[0050] 1) According to the formula requirements, 150 parts by weight of the modified silver nanowires and the polyaniline / silver nanocomposite material in a mass ratio of 1:2.5 were mixed uniformly at room temperature at a speed of 600 r / min for 10 min to obtain component A;
[0051] 2) 100 parts by weight of tetrafunctional epoxy acrylate oligomer, 3 parts by weight of vinyl triethoxysilane, 60 parts by weight of maleic anhydride modified imidazole curing agent and 8 parts by weight of o-hydroxybenzyl dimethylamine were mechanically stirred at 600 r / min for 10 min at room temperature to prepare component B;
[0052] 3) First add component B in a planetary vacuum mixer at room temperature, and then add component A in 4 times, stirring for 10 minutes after each addition, wherein the rotation speed is 500 r / min, the revolution speed is 1000 r / min, and the vacuum degassing mode is turned on during stirring to obtain a conductive rubber material;
[0053] 4) The conductive adhesive prepared in step 3) is injected into a syringe through a vacuum filling machine to obtain a product - a highly heat-resistant and highly thermally conductive conductive silver adhesive.
[0054] Example 2
[0055] This embodiment provides a method for preparing a conductive silver paste with high heat resistance and high thermal conductivity, which comprises the following steps:
[0056] 1) According to the formula requirements, 150 parts by weight of the modified silver nanowires and the polyaniline / silver nanocomposite material in a mass ratio of 1:4 were mixed uniformly at room temperature at a speed of 600 r / min for 10 min to obtain component A;
[0057] 2) 100 parts by weight of tetrafunctional epoxy acrylate oligomer, 5 parts by weight of γ-aminopropylmethyldiethoxysilane, 70 parts by weight of maleic anhydride-modified imidazole curing agent and 10 parts by weight of o-hydroxybenzyldimethylamine were mechanically stirred at room temperature at a speed of 800 r / min for 10 minutes to prepare component B;
[0058] 3) First add component B in a planetary vacuum mixer at room temperature, and then add component A in three times, stirring for 10 minutes after each addition, wherein the rotation speed is 600 r / min, the revolution speed is 1000 r / min, and the vacuum degassing mode is turned on during stirring to obtain a conductive rubber material;
[0059] 4) The conductive adhesive prepared in step 3) is injected into a syringe through a vacuum filling machine to obtain a product - a highly heat-resistant and highly thermally conductive conductive silver adhesive.
[0060] Example 3
[0061] This embodiment provides a method for preparing a conductive silver paste with high heat resistance and high thermal conductivity, which comprises the following steps:
[0062] 1) According to the formula requirements, 330 parts by weight of the modified silver nanowires and the polyaniline / silver nanocomposite material in a mass ratio of 1:3 were mixed uniformly at room temperature with mechanical stirring at a speed of 600 r / min for 10 min to obtain component A;
[0063] 2) 100 parts by weight of tetrafunctional epoxy acrylate oligomer, 8 parts by weight of γ-aminopropyltriethoxysilane, 75 parts by weight of maleic anhydride-modified imidazole curing agent and 12 parts by weight of o-hydroxybenzyldimethylamine were mechanically stirred at 500 r / min for 10 min at room temperature to prepare component B;
[0064] 3) First add component B in a planetary vacuum mixer at room temperature, and then add component A in five times, stirring for 12 minutes after each addition, wherein the rotation speed is 450r / min, the revolution speed is 800r / min, and the vacuum degassing mode is turned on during stirring to obtain a conductive rubber material;
[0065] 4) The conductive adhesive prepared in step 3) is injected into a syringe through a vacuum filling machine to obtain a product - a highly heat-resistant and highly thermally conductive conductive silver adhesive.
[0066] Comparative Example 1
[0067] This comparative example provides a method for preparing a conductive silver paste with high heat resistance and high thermal conductivity, which is basically the same as Example 2, except that unmodified silver nanoparticles and silver nanowires are used.
[0068] Comparative Example 2
[0069] This comparative example provides a method for preparing a conductive silver paste with high heat resistance and high thermal conductivity, which is basically the same as Example 2, except that modified silver nanoparticles and unmodified silver nanowires are used.
[0070] Comparative Example 3
[0071] This comparative example provides a method for preparing a conductive silver paste with high heat resistance and high thermal conductivity, which is basically the same as Example 2, except that modified silver nanowires and unmodified silver nanoparticles are used.
[0072] Performance Test:
[0073] This application takes Example 2 as an example to test the performance of the prepared conductive silver paste, specifically:
[0074] The testing method for the highly heat-resistant and highly thermally conductive conductive silver paste is as follows: pre-cure the conductive silver paste at 90°C for 1 hour, then heat it to 120°C for curing for 1 hour, and finally post-treat it at 130°C for 0.5 hours to ensure that the curing reaction of the epoxy resin / maleic anhydride system is fully carried out. A universal stretching machine is used to test its shear strength (Al-Al / MPa) according to GB7124-2008, the volume resistivity is measured according to ASTMD2739, and the thermal conductivity is measured according to ASTME1461-07; and the product is placed in an outdoor environment for a long time for 12 months for testing to test its storage stability.
[0075] The volume resistivity and bonding strength of the conductive silver glue were tested again and were almost unaffected, showing excellent weather resistance.
[0076] Storage stability: that is, the product of the present invention has high stability and can be used for a long time. The performance test results of Example 2 and Comparative Examples 1-9 are shown in Table 1:
[0077] Table 1 Performance test results of conductive silver paste in Example 2 and comparative examples
[0078]
[0079] It can be seen from the data in Table 1 that the conductive silver paste in the present application not only has excellent electrical conductivity, but also has excellent bonding performance and thermal conductivity; it also has excellent glass transition temperature and thermal decomposition temperature, and has excellent comprehensive performance; it can be seen from the data of Example 1 and Comparative Examples 1-3 that the electrical conductivity and thermal conductivity of the conductive silver paste can be improved by modifying the silver nanoparticles or silver nanowires alone, but the improvement is limited. This may be because the conductive particles at this ratio cannot form a good electrical / thermal conduction path, or the formed electrical / thermal conduction path is limited, and good electrical and thermal conduction properties cannot be obtained, so a higher Only by increasing the filling amount of conductive particles can the conductive properties that meet the product requirements be prepared; and when the silver nanoparticles and silver nanowires are modified at the same time, the dispersion of the conductive particles in the epoxy resin system and the reaction with the epoxy system to form a dense cured adhesive layer, the conductive silver glue system has excellent high glass transition temperature and high thermal decomposition performance. At the same time, the conductive properties and thermal conductivity of the conductive silver glue are synergistically improved; at the same time, because the filling amount of the conductive particles is greatly reduced while preparing the same level of conductive properties, the cost of raw materials is greatly reduced, and the bonding performance and stability of the conductive silver glue system are effectively improved.
[0080] At the same time, the product was placed in an outdoor environment for a long time for 12 months, and the volume resistivity and bonding strength of the conductive silver glue were tested again. It was found that they were almost unaffected, showing excellent weather resistance; that is, the product of the present invention has high stability and can be used for a long time.
[0081] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A highly heat-resistant and highly thermally conductive conductive silver paste, characterized in that: The composition comprises the following components in parts by weight: 100 parts of tetrafunctional epoxy acrylate oligomer, 100-350 parts of conductive particles, 3-8 parts of sintering aid, 60-80 parts of curing agent and 5-15 parts of curing accelerator, wherein the molecular structure of the tetrafunctional epoxy acrylate oligomer is:
2. The highly heat-resistant and highly thermally conductive conductive silver paste according to claim 1, characterized in that: The curing agent is a maleic anhydride modified imidazole curing agent.
3. The highly heat-resistant and highly thermally conductive conductive silver paste according to claim 1, characterized in that: The conductive particles include a mixture of silver nanocomposite particles and silver nanowires in a mass ratio of 1:(2-5); wherein the particle size of the silver nanocomposite particles is 5-30 nm; and the size of the silver nanowires is 5-10 nm.
4. The highly heat-resistant and highly thermally conductive conductive silver paste according to claim 3, characterized in that: The conductive particles are characterized in that the silver nanocomposite particles are obtained by the following preparation method: a. Sodium hypophosphite was dissolved in distilled water and dispersed evenly by ultrasonication, and then a nitric acid solution containing aniline was added to the solution to prepare a reducing solution; silver nitrate was weighed and dissolved in water and added to the nitric acid solution and stirred to prepare an oxidizing solution, which was then added dropwise to the reducing solution to prepare silver nanoparticles, and the reaction was stirred to proceed; b. After the reaction in step a is completed, the reaction system is moved to room temperature. After the system temperature stabilizes, an aqueous solution containing nitric acid and ammonium persulfate is added dropwise to the reaction solution to initiate in-situ polymerization of aniline to obtain a polyaniline / silver nanocomposite material, namely, silver nanocomposite particles.
5. The highly heat-resistant and highly thermally conductive conductive silver paste according to claim 3, characterized in that: The silver nanowires are pretreated by the following method: octadecyl-polyethylene glycol-thiol is added to water, stirred and dispersed evenly, the silver nanowires are immersed in the aqueous solution of octadecyl-polyethylene glycol-thiol, then heated and dried, and then immersed in water again, repeated three to five times, and finally heated and dried to obtain the modified silver nanowires.
6. The highly heat-resistant and highly thermally conductive conductive silver paste according to claim 1, characterized in that: The sintering aid is a silane coupling agent, and the silane coupling agent is one or a mixture of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, and vinyltriethoxysilane.
7. The highly heat-resistant and highly thermally conductive conductive silver paste according to claim 6, characterized in that: The curing accelerator is at least one of 2,4,6-tris(dimethylaminomethyl)phenol, o-hydroxybenzyldimethylamine, benzyldimethylamine or nonylphenol.
8. A method for preparing the highly heat-resistant and highly thermally conductive conductive silver paste according to any one of claims 1 to 7, characterized in that: The steps include: 1) preparing modified silver nanowires; 2) Preparation of polyaniline / silver nanocomposites; 3) According to the formula requirements, the modified silver nanowires in step 1) and the polyaniline / silver nanocomposite material prepared in step 2) are mixed uniformly to obtain component A; 4) mechanically stirring the tetrafunctional epoxy acrylate oligomer, sintering aid, curing agent and curing agent accelerator at room temperature at a speed of 500-1000 r / min for 10 min to prepare component B; 5) First add component B in a planetary vacuum mixer at room temperature, then add component A in 2-5 times, stir for 5-15 minutes after each addition, wherein the rotation speed is 300-800 r / min, the revolution speed is 800-1500 r / min, and the vacuum degassing mode is turned on during stirring to obtain a conductive rubber material; 6) The conductive adhesive prepared in step 5) is injected into a syringe through a vacuum filling machine to obtain a product - a highly heat-resistant and highly thermally conductive conductive silver adhesive.